A removable functional group strategy for regiodivergent Wittig rearrangement products. Issue 46 (15th November 2018) - Alam, Md Nirshad; K. M., Lakshmi; Maity, Pradip
Abstract : Controlling anionic pericyclic [2, 3] Wittig and bis-radical [1, 2] Wittig reactions for unprecedented regiodivergency via a single removable functional group. Abstract : [1, 2] and [2, 3] Wittig rearrangements are competing reaction pathways, often leading to uncontrollable product distribution. We employ a single removable functional group to fulfill the dual role of attaining a reversible [2, 3] and stabilizing radical intermediate for the [1, 2] path to obtain both the Wittig products selectively for a broad range of substrates.